STUDY OF HETEROSIS AND COMBINING ABILITY FOR YIELD AND YIELD CONTRIBUTING TRAITS IN BARLEY (HORDEUM VULGARE L.) - K. R. POTLA; S. S. BORNARE; L. C. PRASAD; R. PRASAD; A. H. MADAKEMOHEKAR (The Bioscan, 2013)
Thirteen diverse barley genotypes were selected and crossed in a line × tester fashion to evaluate combining ability and heterosis to identify promising hybrids for ten quantitative traits including yield and its components. Analysis of variance for line x tester reveals highly significant differences for most of the characters investigated. The combining ability analysis showed significant differences among the parents for GCA, among crosses for SCA for all the quantitative traits respectively. Among the parents, tester namely RD-2508 and lines INBON-65, INBON-18, Beecher, Rihane, Moroc-9-75, 11th HBSN-146 and HUB-174 were good general combiners for grain yield and its component traits. While among crosses, cross IBNON-65 × RD-2508 was recorded highest magnitude of economic heterosis over the best standard check viz., K- 603 for grain yield. As per SCA effects, the crosses viz.,11th HBSN-146 x Lakhan for grain yield per plant and Rihane x Lakhan for 1000 grain weight were most promising. It is, therefore, the selective parents and crosses could be utilized for developing desirable genotypes/hybrids/varieties with better yielding towards exploiting the hybrid vigor or other associated traits under crop improvement.